NOTARY COMPETENCY AS AN AWQAF DECLARARATION DEED MAKER IN SHARE ACQUISITION - Lita Paromita Siregar (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
Other Than Money Through Awaqf (MoRA Regulation on Movable Awqaf governs notary may act as Awqaf Declaration Deed Maker (ADDMF) once he obtains permit from MoRA after mastering competency in awqaf sector proven by certification. However, to date no notary has ever acquired that certification because the MoRA has not yet set and issue any regulation relating to that competency. This aim of this research is to explore the competencies that must be mastered by notary to act as an ADDMF and to explore the impact if the Awqaf Declaration Deed is not made in form of notarial deed using juridical-empirical methodology. This research indicates as a PPAIW, notary must master in 5 competencies, namely: 1. Shariah and positive law competency of awqaf, 2. Company Law, 3. Capital Market, 4. Awqaf Declaration Deed Drafting and, 5. Money Laundering. Further, if an acquisition happens but the Awqaf Declaration Deed is not made in notarial form, then Ministry of Law and Law will not accept any amendment of articles of association or company data from the shareholders whose acquisition are not obtaining approval from Ministry of Law and Human Rights.